2015
DOI: 10.1158/2326-6066.cir-14-0202
|View full text |Cite
|
Sign up to set email alerts
|

Resiquimod as an Immunologic Adjuvant for NY-ESO-1 Protein Vaccination in Patients with High-Risk Melanoma

Abstract: The TLR7/8 agonist, Resiquimod has been used as an immune adjuvant in cancer vaccines. We evaluated the safety and immunogenicity of the cancer testis antigen NY-ESO-1 given in combination with Montanide with or without Resiquimod in high-risk melanoma patients. In Part I of the study, patients received 100ug full length NY-ESO-1 protein emulsified in 1.25mL Montanide (day 1) followed by topical application of 1000mg of 0.2% Resiquimod gel on days 1 and 3 (Cohort 1) versus days 1, 3, and 5 (Cohort 2) of a 21 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 46 publications
1
72
0
Order By: Relevance
“…Of the cancers investigated to date, this effect is most pronounced in ovarian cancer cells (16). Treatment of ovarian cancer cells with the DNA methyltransferase inhibitor DAC (17) results in expression of cancer-testis antigens and MHC class I, increasing cancer cell recognition by CD8 þ T cells (18). DAC similarly restores expression of cytokines, cancer-testis antigens, MHC class I and II, and costimulatory molecules in cancer patients (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Of the cancers investigated to date, this effect is most pronounced in ovarian cancer cells (16). Treatment of ovarian cancer cells with the DNA methyltransferase inhibitor DAC (17) results in expression of cancer-testis antigens and MHC class I, increasing cancer cell recognition by CD8 þ T cells (18). DAC similarly restores expression of cytokines, cancer-testis antigens, MHC class I and II, and costimulatory molecules in cancer patients (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Peptide-based vaccination was employed as a standalone adjuvanted intervention, 140-146 or combined with chemotherapy 147-149 radiation therapy 147,150 or other forms of treatment including other immunotherapies. 148,149,151-158 These studies enrolled patients with hematological malignancies, 151,159 brain tumors, 152,153 non-small cell lung carcinoma (NSCLC), 140,147,160 breast cancer, 141,148,161 , prostate carcinoma, 142,154 melanoma, 144-146,155-158,162 . ovarian cancer.…”
Section: Literature Updatementioning
confidence: 99%
“…149 , cervical cancer, 163 hepatocellular carcinoma 164 and biliary tract cancer 165 . The TAAs harnessed for the construction of peptide-based vaccines in these studies included the cancer/testis antigen 1B (CTAG1B; best known as NY-ESO-1), 144 MAGE family member A3 (MAGEA3), 140,146,147 TTK protein kinase (TTK), 158 WT1, 151,166 baculoviral IAP repeat containing 5 (BIRC5; best known as survivin), 149 mutant epidermal growth factor receptor (EGFRvIII), 153 erb-b2 receptor tyrosine kinase 2 (ERBB2; best known as HER2), 148 indoleamine 2,3 dioxygenase 1 (IDO1), 157 TCR gamma alternative reading frame protein (TARP), 154 and multiple glioma-associated antigens. 152 Most often, peptide-based vaccines were well tolerated and no severe side effects were reported.…”
Section: Literature Updatementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, by contrast to imiquimod, resiquimod may be orally administered (60). Resiquimod may be considered as a potential cancer vaccine adjuvant due to its ability to increase antigen presentation via the direct activation of dendritic cells (DCs), determine local activation of immune cells and enhance the production of pro-inflammatory cytokines and the subsequent transcription of NF-κB and type I IFN (62). A previous study revealed that combined treatment with NY-ESO-1 antigens (a frequently expressed tumor-specific antigen that stimulate humoral and cellular immune responses in cancer patients), Montanide (an immune adjuvant that ensures the slow release of antigens and the recruitment of antigen-presenting cells to the injection site) and topical resiquimod results in high immunogenicity in melanoma patients.…”
Section: Imiquimod In Lmmentioning
confidence: 99%